DETERMINING THE RELATIONSHIP BETWEEN HIGH SCHOOL STUDENTS' ATTITUDES TOWARDS PHYSICAL EDUCATION COURSE, HUMAN VALUES AND BODILY INTELLIGENCE - Gökyürek, Belgin; Ayyildiz Durhan, Tebessüm (Acta Scientiae et Intellectus, 2024)
The aim of this study is to determine the relationship between high school students' attitudes towards physical education course, human values and bodily intelligence, and to analyze the differences between various variables and measurement tools. A total of 471 students studying at 4 different high schools participated in the study, and the data belonging to the study group were collected with the "Physical Education Course Attitude Scale", the "Human Values Scale (HVS)" scale and the "Bodily/Kinesthetic Intelligence Scale". In the analysis of the data, descriptive statistics have been evaluated with independent sample t-test, one-way analysis of variance Anova, post hoc tests and pearson correlation analysis. When the research findings were examined, it has been determined that the participants exhibited a high level of attitude, human values and bodily intelligence. At the same time, it has been determined that students' attitudes towards physical education course, human values and bodily intelligence show significant differences with variables such as gender, grade, school, income, exercising or doing sports outside of school, exercising regularly in a club. In addition, it has been concluded that there has been a significant positive correlation between the measurement tools. As a result, it can be said that students' attitudes towards physical education course, human values and bodily intelligence are high and certain variables significantly differentiate these levels.